Dinosaur Detectives - PETER CHRISP
This introduction to paleontology weaves together facts about fossil hunting with fictionalized first-person accounts from dinosaur detectives. Track dinosaurs with the earliest fossil hunters and modern-day geologists! Read about their amazing discoveries.